2016
DOI: 10.1007/s10071-016-1057-3
|View full text |Cite
|
Sign up to set email alerts
|

Global/local processing of hierarchical visual stimuli in a conflict–choice task by capuchin monkeys (Sapajus spp.)

Abstract: Acknowledgements 21We thank two anonymous reviewers for their thoughtful suggestions and constructive comments on 22 the manuscript. We are also grateful to Tyrone Lucon Xiccato for his helpful statistical suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Interestingly, a prevalence of global over local feature processing—the so-called global precedence effect (Navon, 1977)—that was shown in (western) humans could not be found in baboons (Fagot & Deruelle, 1997). Data from capuchin monkeys also suggest a more locally oriented processing style (Spinozzi et al, 2006; Truppa et al, 2016, 2017). Whereas these monkey subjects primarily process the local features of a stimulus array, chimpanzees seem to fall in between humans and monkeys depending on the presentation format used.…”
mentioning
confidence: 98%
“…Interestingly, a prevalence of global over local feature processing—the so-called global precedence effect (Navon, 1977)—that was shown in (western) humans could not be found in baboons (Fagot & Deruelle, 1997). Data from capuchin monkeys also suggest a more locally oriented processing style (Spinozzi et al, 2006; Truppa et al, 2016, 2017). Whereas these monkey subjects primarily process the local features of a stimulus array, chimpanzees seem to fall in between humans and monkeys depending on the presentation format used.…”
mentioning
confidence: 98%
“…Research on perceptual grouping has extensively examined two levels of hierarchical processing, centering on the relative primacy of global features versus local features within a scene [ 1 6 ]. Global processing involves integrating various elements into a coherent whole, while local processing concentrates on the finer details of a prominent object or situation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies exploring perceptual grouping processes with visual stimuli reveal variations in the precedence of global or local cues across different species, including humans [ 9 11 ], chimpanzees [ 3 , 11 , 12 ], baboons [ 10 ], rhesus monkeys [ 12 ], cotton top tamarins [ 13 ], and capuchin monkeys [ 6 , 9 , 14 ]. In the context of platyrrhine monkeys, investigations into global and local processing have predominantly focused on capuchin monkeys [ 1 , 5 , 6 , 9 , 14 19 ]. Several of these experiments utilized matching-to-sample (MTS) procedures, and their outcomes consistently demonstrated an advantage for local level of hierarchical processing [ 1 , 14 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the question of configural/holistic processing for other visual objects has been mainly investigated by using Navon-like hierarchical stimuli (stimuli showing a global shape or configuration created by the spatial arrangement of local shapes). Most tested species demonstrated a preference to process local information rather than the global configuration [e.g., baboons ( Fagot and Deruelle, 1997 ), capuchin monkeys ( Truppa et al, 2017 ), or chicks ( Chiandetti et al, 2014 )]. To date, only Humans ( Navon, 1977 ), a fish species Xenotoca eiseni ( Truppa et al, 2010 ) and honeybees ( Avarguès-Weber et al, 2015 ) showed consistent global preference suggesting a general importance of visual configural processing in these species.…”
Section: Introductionmentioning
confidence: 99%